2024
DOI: 10.1002/adfm.202310283
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Role of Ligand Engineering on Local and Macroscopic Charge‐Carrier Transport in NaBiS2 Nanocrystal Thin Films

Yi‐Teng Huang,
Markus Schleuning,
Hannes Hempel
et al.

Abstract: Ternary chalcogenides have emerged as potential candidates for ultrathin photovoltaics, and NaBiS2 nanocrystals (NCs) have gained appeal because of their months‐long phase‐stability in air, high absorption coefficients >105 cm−1, and a pseudo‐direct bandgap of 1.4 eV. However, previous investigations into NaBiS2 NCs used long‐chain organic ligands separating individual NCs during synthesis, which severely limits macroscopic charge‐carrier transport. In this work, these long‐chain ligands are exchanged for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Valakh et al have shown that when a Cu 2 ZnSnS 4 particle was excited by a high-power 514.5 nm wavelength laser, its Raman peaks shifted and broadened, indicating an increased degree of cation disorder. 64 In terms of the impact of an applied electric field on cation disorder, although a direct investigation has not yet been reported, significant ion migration has been observed in AgBiS 2 and NaBiS 2 devices under bias, 65,66 suggesting that the cations may be mobile. Nevertheless, more quantitative investigations will be needed to verify the effectiveness and reproducibility of these light- or electric field-induced changes in cation disorder.…”
Section: Strategies To Tune Cation Disordermentioning
confidence: 99%
“…Valakh et al have shown that when a Cu 2 ZnSnS 4 particle was excited by a high-power 514.5 nm wavelength laser, its Raman peaks shifted and broadened, indicating an increased degree of cation disorder. 64 In terms of the impact of an applied electric field on cation disorder, although a direct investigation has not yet been reported, significant ion migration has been observed in AgBiS 2 and NaBiS 2 devices under bias, 65,66 suggesting that the cations may be mobile. Nevertheless, more quantitative investigations will be needed to verify the effectiveness and reproducibility of these light- or electric field-induced changes in cation disorder.…”
Section: Strategies To Tune Cation Disordermentioning
confidence: 99%